Pelatihan Kreasi Buket Bunga Untuk Menumbuhkan Keterampilan Kewirausahaan di Masyarakat Kelurahan Beras Basah - Rizki Nurjehan; Nabillah Hafiz Warista PA; Faisal Efendi; Muhammad Rahmat (Fusion: Jurnal Pengabdian kepada Masyarakat, 2023)
Based on our research in Beras Basah Village so many housewife is not have a job. So the researchers aim to make flower bouquet entrepreneurship training to increase their income. We use qualitative method, the population is housewife in organitation PKK at Beras Basah village, and the sample of 20 people.This research has a positive impact on their creativity. This can be seen from their enthusiastic attitude in participating in the training. The researcher's recommendation for this activity is to develop it independently and sustainably so that it can grow new UMKM